2020
DOI: 10.3168/jds.2018-15930
|View full text |Cite
|
Sign up to set email alerts
|

Energy requirements and efficiency of energy utilization in growing dairy goats of different sexes

Abstract: The aim of this study was to investigate the effects of sex on the requirements for maintenance and efficiency of energy utilization in growing Saanen goats. A database from 7 comparative slaughter studies that included 238 Saanen goats was gathered to provide information for the development of prediction equations of energy requirements for maintenance and efficiency of energy utilization. The experimental design provided different levels of metabolizable energy intake (MEI) and empty body weight (EBW). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In the offered diet and orts, the dry matter (DM), organic matter (OM), neutral detergent fiber (NDF), and indigestible NDF (iNDF) concentration were determined, and posteriorly intake of DM (DMI), OM (OMI), NDF (NDFI), iNDF (iNDFI), potentially degradable NDF (pdNDFI) were calculated. In addition, we calculated the feeding level as multiples of metabolizable energy (ME) requirements for maintenance intake (L), using ME requirements for maintenance of growing Saanen goats ( Souza et al, 2020 ). The ME in the diet was estimated when goats were around 22 and 37 kg BW for study ( Leite et al, 2015a , 2015b ) and ( Silva, 2013 ), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the offered diet and orts, the dry matter (DM), organic matter (OM), neutral detergent fiber (NDF), and indigestible NDF (iNDF) concentration were determined, and posteriorly intake of DM (DMI), OM (OMI), NDF (NDFI), iNDF (iNDFI), potentially degradable NDF (pdNDFI) were calculated. In addition, we calculated the feeding level as multiples of metabolizable energy (ME) requirements for maintenance intake (L), using ME requirements for maintenance of growing Saanen goats ( Souza et al, 2020 ). The ME in the diet was estimated when goats were around 22 and 37 kg BW for study ( Leite et al, 2015a , 2015b ) and ( Silva, 2013 ), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The ME concentration in the diet (kcal/kg of DM) was estimated from gross energy intake, total energy losses from feces, urine, and gaseous products of digestion. Fecal and urinary excretions were obtained from their total collection ( Souza et al, 2020 ). Energy loss from gaseous products of digestion was predicted according to Blaxter and Clapperton (1965) equation, as described by Souza et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that sex (Souza et al, 2017) and breed (Taylor, 1980) differences in body composition at the same BW shrink when comparing animals at the same degree of maturity. Likewise, methods to overcome genotype effect due to differences in maturity degree on nutritional requirements have been applied (Souza et al, 2020) while considering the comparative slaughter technique. In this sense, Emmans (1989) suggested to describe and evaluate different genotypes using potential protein growth, enabling the identification of genotypic differences in energy content.…”
Section: Introductionmentioning
confidence: 99%